(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we apply a recently proposed thermal axisymmetric lattice Boltzmann model to the thermocapillary driven flow in a cylindrical container. The temperature profiles and isothermal lines at the free surface with Prandtl (Pr) number fixed at 0.01 and Marangoni (Ma) number varying from 10 to 500 are measured and compared with the previous numerical results. In addition, we also give the numerical results for different Ma numbers at Pr=1.0. It is shown that present results agree well with those reported in previous studies.